Mediating Role of Work Motivation in the Relationship of Career Development and Distributive Justice with Employee Performance among Cosmetics Sector Employees - Kodija Kodija; Fakhry Ardhusyarif; Dedi Muhammad Sidiq; James Tembo (Universitas KH. Abdul Chalim Mojokerto, 2026)
Employee performance is a crucial factor in achieving organizational goals. However, performance can be influenced by various organizational factors, such as career development and distributive justice. Despite numerous studies on these topics, the role of work motivation as a mediating variable remains underexplored. This raises the question: does work motivation mediate the effect of career development and distributive justice on employee performance? This study aims to examine the effect of career development and distributive justice on employee performance, with work motivation as a mediating variable. A quantitative research approach was used, employing Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method through SmartPLS 3.0 software. Data were collected from 115 employees in the cosmetics sector in Cirebon, Indonesia, using a structured questionnaire. The results show that career development and distributive justice both have a positive and significant effect on employee performance and work motivation. Additionally, work motivation significantly mediates the relationship between career development and distributive justice on employee performance. These findings suggest that organizations should pay greater attention to fairness in resource distribution and provide structured career development programs to enhance motivation, which in turn improves employee performance. This study contributes to the literature by emphasizing the role of motivation as a key mediator between organizational practices and performance outcomes.